LE RÔLE DE L’EXCEPTION DANS LA DISSOCIATION DES NOTIONS - Alice TOMA (Diversitate si Identitate Culturala in Europa)
The dissociation of concepts is an essential part of argumentation. The interpretation and reinterpretation of a concept leads, in general, to the dissociation of concepts. The argumentative conflict becomes a language conflict. We first present and discuss the sense given to the dissociation of notions by the Brussels school, starting with Perelman & Olbrechts-Tyteca, continuing with Marc Dominicy and Emmanuelle Danblon, following also the echoes generated especially in M. A. van Rees of the Amsterdam school. Is the notion of dissociation of concepts used without being prescriptive? Does the dissociation of concepts retain – following a critical movement – the positive part of the ethical standard by removing the negative part rejected by the universal audience? Or is the dissociation of concepts useful to establish whether an argument is valid or false? Which epistemology of the argument? In a second step we focus on a mechanism that seems to lead to the dissociation of notions, the exception, and propose also an analysis of its textual linguistic features.